Implementation of Telemedicine in Sports Medicine: Digital Approach to Prevention, Diagnosis, and Rehabilitation - Sinanović, Šćepan; Milić, Marko Kimi; Slobodan (Sport - nauka i praksa, 2025)
Telemedicine has become a key tool in modern healthcare, enabling remote access to medical services. In sports medicine, its application brings significant innovations in the prevention, diagnosis, and rehabilitation of sports injuries. This study examines the effectiveness of telemedicine technologies by analyzing their contributions to the reduction of injury incidence, improvement of diagnostic accuracy, and acceleration of recovery time. The research included a sample of 150 professional and amateur athletes, utilizing wearable devices, activity-tracking applications, and remote consultation platforms. Statistical data analysis demonstrated that telemedicine can reduce injury incidence by 25% and shorten the average rehabilitation duration by 30%. The results also indicate increased athlete satisfaction with treatment, contributing to a faster return to activities. It was concluded that telemedicine offers practical solutions to challenges in sports medicine, particularly in remote areas with limited access to specialized care. However, further research is needed to overcome technical and ethical challenges. These findings provide a foundation for further development of telemedicine platforms tailored to the specific needs of athletes.